Impacts of Soot, Ash, Sand, and Haze on Snow Albedo in Sierra Nevada, Spain - Sofía González-Correa; Magín Lapuerta; Rosario Ballesteros; Diego Pacheco-Ferrada; Lina Castro; Francisco Cereceda-Balic (Atmosphere, 2022)
Snow covers are greatly affected by particles deposited on their surface. In this work, an experimental campaign was carried out in the Sierra Nevada (Granada, Spain). The optical effect of different contaminating particles on the snow covers was measured using a field spectroradiometric system composed of three upwelling spectroradiometers and three downwelling ones. Sand collected from a Mediterranean beach (Spain), ash collected from the La Palma volcano eruption, haze collected from an event that occurred in Spain, and soot collected from a diesel vehicle were employed for contaminating the snow. Soot, ash, and sand were analysed with X-ray diffraction to obtain their mineralogical composition or their structural characteristics, whereas haze's mineralogical composition was obtained from the literature. From this information, the refractive index of each material was weigh-averaged, considering the refractive indices of their components. After measurements, snow samples were filtered and weighted to evaluate the particle concentrations in the snow. Previous contamination with soot was observed due to the existence of a nearby road. Snow albedo was calculated with the OptiPar model. The experimental and modelled results show that contaminating with sand decreases the snow albedo in the visible range whereas it increases the albedo in the infrared range. However, the rest of the materials lead to a decrease in the albedo in the whole spectrum, although with different intensities depending on the wavelength range.